2017
DOI: 10.1111/1440-1681.12894
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of riboflavin on acetic acid‐induced colonic injury in rats

Abstract: Riboflavin (RF) has been found to be a promising antioxidant and/or anti-inflammatory agent in several studies. However, the effect of RF against acetic acid (AA)-induced colonic injury is currently unknown. This study aimed to investigate the potential antioxidant and protective effects of RF in a rat model of ulcerative colitis. Starting immediately after the colitis induction (AA+RF group) or 1 week before the colitis induction (RF+AA+RF group), the rats were treated with RF (25 mg/kg per day; p.o.) for 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…B. acidifaciens is also known to increase SCFA production of acetic and succinic acids, both of which can contribute to colitis‐associated inflammation. Acetic acid, given in high concentrations, can induce colitis in murine models . Succinic acid, which is produced by members of Bacteroidacea e, such as B. acidifaciens , was found to be increased in the colons of colitis‐induced mice and when administered by enemas can produce ulcers in the colon .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. acidifaciens is also known to increase SCFA production of acetic and succinic acids, both of which can contribute to colitis‐associated inflammation. Acetic acid, given in high concentrations, can induce colitis in murine models . Succinic acid, which is produced by members of Bacteroidacea e, such as B. acidifaciens , was found to be increased in the colons of colitis‐induced mice and when administered by enemas can produce ulcers in the colon .…”
Section: Discussionmentioning
confidence: 99%
“…Acetic acid, given in high concentrations, can induce colitis in murine models. 57 Succinic acid, which is produced by members of Bacteroidaceae, such as B. acidifaciens, was found to be increased in the colons of colitis-induced mice and when administered by enemas can produce ulcers in the colon. 58 B. acidifaciens resembles closely another member of the same genus B. fragilis, and these bacteria have been shown in the literature to trigger a strong inflammatory cascade response, including activation of IL-17dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…8-OHdG, which is formed by the reaction of OH radical, the strongest reactive oxygen species, with guanine base, is known as an indicator of oxidative DNA damage [21]. Various studies have shown that oxidative stress increases the formation of 8-OHdG [21,22]. In this study, ischemia/reperfusion in kidney tissues increased oxidative DNA damage as assessed by increased 8-OHdG levels while this increase is reversed by riboflavin treatment.…”
Section: Discussionmentioning
confidence: 57%
“…DNA damage is induced by cellular metabolites such as ROS or exogenous agents and may be cause mutation, aging or death of cell. 8-OHdG, which is formed by the reaction of OH radical, the strongest reactive oxygen species, with guanine base, is known as an indicator of oxidative DNA damage [21]. Various studies have shown that oxidative stress increases the formation of 8-OHdG [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the importance of excess and uncontrollable Reactive Oxygen Species (ROS) in the pathogenesis of ulcerative colitis, the value to determine free radical scavenger such as reduced Glutathione. The endogenous antioxidant GSH was reduced significantly in the colonic tissues of the acetic acid-induced ulcerative colitis in rats (Karakoyun et al, 2018). Colon Caspase-3 levels were higher in the colitis than in the control group rats (Akcan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%